2018
DOI: 10.22603/ssrr.2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Kyphotic Deformity after Laminoplasty in Patients with Cervical Ossification of Posterior Longitudinal Ligament with Normal Sagittal Spinal Alignment

Abstract: 1Background: Preoperative cervico-thoracic kyphosis and cervical regional positive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In patients who underwent laminoplasty, we did not encounter serious cases of cervical deformity, as described by Matsuoka, after expansive laminoplasty. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients who underwent laminoplasty, we did not encounter serious cases of cervical deformity, as described by Matsuoka, after expansive laminoplasty. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 19 ] In other words, in the example given by Matsuoka, reducing the T1 slope angle corrects all spinopelvic parameters, and this is a controversial situation. [ 9 ] In such a patient, naturally, by performing lumbar or thoracic osteotomy, it will be a better choice for the improvement of cervical deformity. [ 20 21 22 ] In patients undergoing decompression and fusion due to cervical stenosis, it is very important to protect cervical parameters; otherwise, HRQOL can also cause serious disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory responses are known as a major component of secondary injury of initial ischemic insult and play an important role in modulating the pathogenesis of C5 palsy [37,8,24,20]. Effects of reperfusion, also known as reperfusion injury, are the causative factors for spinal edema [38,25,8,18]. The results of this study shown the complication of C5 palsy in PCDL were serve than ACCF may be related the spinal ischemia and reperfusion injury.…”
Section: Discussionmentioning
confidence: 58%
“…To evaluate cervical sagittal balance, we measured the following parameters on cervical lateral X-ray: C2-7 SVA, T1 slope, CL, and T1 slope-CL. The C2-7 SVA was defined as the total distance from the plumb line of the pedicle center of the C2 vertebra to the posterior superior corner of the C7 vertebra [14]. The CL was measured using the Cobb angle of C2 lower endplate and C7 lower endplate [15].…”
Section: Methodsmentioning
confidence: 99%